MENGURAI DAMPAK KETELADANAN GEMBALA SIDANG PADA PERTUMBUHAN GEREJA - Kadun, Satria Omega (Shift Key : Jurnal Teologi dan Pelayanan, 2023)
Pastor is a leader who is specially called by God to carry out the task of serving the congregation to guide their faith in God. Thus, the example of the pastor will affect the growth of the church. The method used is library research with a qualitative research type approach. The data sources are collected using books and journal articles related to the theme, so as to obtain an overview of the impact of the example of a pastor on church growth. With the pastor's example, faithfulness in worship and the congregation's attendance in worship will increase (growing in number).